The Implementation of the Inquiry-Based Learning Model in Improving Elementary School Students' Numeracy and Literacy Skills - Tiara Maharani Suroso; Agata Pritha Kinanditya (CV. Akademi Merdeka, 2026)
This study analyzes the effect of the inquiry-based learning model on elementary school students’ numeracy literacy skills. Using a pre-experimental one-group pretest–posttest design with 30 fifth-grade students, data were collected via essay-based tests. The results showed a significant increase in numeracy literacy, with the average score rising from 59.77 on the pretest to 82.53 on the posttest. Statistical validation through a paired-samples t-test yielded a t-value of -145.275 (p < 0.05), confirming that the improvement was not due to random chance. Furthermore, an N-Gain analysis of 0.788 indicates a high level of improvement. Deeper analysis using the Pearson product–moment correlation revealed a very strong positive relationship of 0.991 (p = 0.000) between pretest and posttest scores. This demonstrates that student progress was highly consistent across the group, meaning the intervention effectively benefited both high- and low-achieving students similarly. These findings suggest that inquiry-based learning effectively enhances numeracy literacy by encouraging active involvement and contextual problem-solving.